2018
DOI: 10.1039/c8cp02516a
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of Ni incorporation into Fe3O4(001)

Abstract: The normal incidence X-ray standing wave (NIXSW) technique has been used to follow the evolution of the adsorption geometry of Ni adatoms on the Fe3O4(001)-(√2 × √2)R45° surface as a function of temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…Isolated Ir 1 adatoms appear as bright protrusions between the rows, as has been observed previously for a variety of other metals on this surface . The adsorption site is essentially where the next tetrahedrally coordinated Fe cation would reside in the spinel structure, suggesting a two‐fold coordination to the substrate. This is in line with our DFT calculations (optB88‐DF, U eff =3.61 eV), which find a strong binding energy (−5.2 eV with respect to a single Ir atom in the gas phase) and small positive Bader charge of 0.5 e for an Ir adatom in this position.…”
Section: Resultsmentioning
confidence: 97%
“…Isolated Ir 1 adatoms appear as bright protrusions between the rows, as has been observed previously for a variety of other metals on this surface . The adsorption site is essentially where the next tetrahedrally coordinated Fe cation would reside in the spinel structure, suggesting a two‐fold coordination to the substrate. This is in line with our DFT calculations (optB88‐DF, U eff =3.61 eV), which find a strong binding energy (−5.2 eV with respect to a single Ir atom in the gas phase) and small positive Bader charge of 0.5 e for an Ir adatom in this position.…”
Section: Resultsmentioning
confidence: 97%
“…The sample plate was attached to the liquid-He cryostat via Ta rods, and the temperature was measured by a K-type thermocouple spot-welded on the sample plate. A molecular beam is formed by expansion of 0.53 mbar 18 O 2 or 0.27 mbar 13 CO through two differentially pumped stages. This results in a well-defined beam spot on the sample surface with a diameter of 3.35 ± 0.17 mm and a top-hat intensity profile.…”
Section: Methodsmentioning
confidence: 99%
“…Such a phenomenon has been observed for several different metal adatoms on Fe 3 O 4 (001) before and the foreign adatom can either substitute a 5-fold coordinated surface Fe oct or incorporate in the vacant octahedral site of the SCV reconstruction. [13][14][15]29 Schematic representations of the three possible sites of Rh 1 near the surface are shown in insets in Fig. 2a.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes sense because Ag and Cu are twofold coordinated to oxygen in Ag 2 O and Cu 2 O. In a followup study [11], we found that Ni is relatively unstable in the twofold geometry, and moves to occupy a subsurface octahedral site with higher oxidation state upon mild annealing. This experiment confirmed our inference from scanning tunnelling microscopy (STM) and xray photoelec tron data for a range of 3d transition metals [12], which showed the adatoms disappearing into the oxide.…”
Section: Einsicht In Die Einzelatomkatalyse -Vakuumexperimente An Modmentioning
confidence: 82%